Mosby's 2013 nursing drug database - Skidmore-Roth, Linda; Mosby, Inc. ([St. Louis, MO] : Mosby, 2013)
Includes more than 1,300 generic and 4,500 trade drugs from Mosby's 2000 nursing drug reference. Detailed drug monographs include action and uses, dosage, side effects/adverse reactions, and much more. Allows searching for drugs by generic or trade names.
Title from opening screen.
User's guide (18 p. ; 12 cm.) inserted in container.
System requirements: 486 or Pentium PC; Windows 95, 98 or NT; 16 MB RAM (32 MB recommended); 30 MB free hard disk space; 4X or faster CD-ROM drive; 640 x 480 color monitor with 256 colors or better; 28.8 or faster modem (optional for Internet access).
Keywords: Drugs -- Handbooks, manuals, etc; Nursing -- Handbooks, manuals, etc